The Effect of Promotion with Flipchart Media on Toothbrush Knowledge Levels of Maintaining Dental and Oral Health in Children - Haryani, Wiworo; Sulastri, Siti (JURNAL INFO KESEHATAN, 2022)
Elementary school children possess a high risk of dental caries. Based on the Basic Health Research 2018 data, the percentage of dental and oral health problems in the 10–14 year age group is 41.4%. Efforts to reduce dental and oral health problems in children are conducted by health promotion which can be implemented with flipchart media. Flipchart media can be an alternative; hence, elementary school children are able to better understand the importance of knowledge on maintaining oral health. The objective of this study is to determine the effect of promotion with flipcharts on the level of toothbrush knowledge of maintaining oral and dental health in children. This type of research was a quasi-experimental with a pretest-posttest design with control group. The research location is at SD Muhammadiyah Banyuraden, Gamping, Sleman, Yogyakarta. The research sample is 80 children aged 8 to 12 years. The sampling technique employed purposive sampling. The influence variable is promotion with flipchart, and the affected variable is the level of knowledge in maintaining oral health. The treatment and control groups performed pretest and posttest to determine the level of knowledge of dental and oral care in elementary school children. The results of the Wilcoxon Signed Rank Test analysis demonstrated that before and after promotion, the two groups owned a significant difference in toothbrush knowledge level (p=0.00). The results of the Mann Whitney test analysis display that the mean rank of children's toothbrush knowledge level using flipchart media is greater than PowerPoint media, which is 58.03> 20.98 so that it can be stated that the use of flipchart media is more effective than PowerPoint media. The conclusion of the study is that promotion by employing flipchart media can increase the level of toothbrush knowledge on maintaining oral and dental health in children.